The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1016/s0005-2728(00)00277-2
|View full text |Cite
|
Sign up to set email alerts
|

Structure–function relationships of Na+, K+, ATP, or Mg2+ binding and energy transduction in Na,K-ATPase

Abstract: The focus of this article is on progress in establishing structure-function relationships through site-directed mutagenesis and direct binding assay of Tl(+), Rb(+), K(+), Na(+), Mg(2+) or free ATP at equilibrium in Na,K-ATPase. Direct binding may identify residues coordinating cations in the E(2)[2K] or E(1)P[3Na] forms of the ping-pong reaction sequence and allow estimates of their contributions to the change of Gibbs free energy of binding. This is required to understand the molecular basis for the pronounc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
74
0
16

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(95 citation statements)
references
References 70 publications
5
74
0
16
Order By: Relevance
“…The true effect on Na ϩ binding to E 1 may actually be more pronounced than revealed by the 3-fold decrease in apparent affinity, because it is masked by displacement of the conformational equilibrium in favor of E 1 . The 3-fold reduction or more of Na ϩ affinity is of the same magnitude as previously detected for some of the mutants with alterations to residues proposed to contribute to coordination of Na ϩ in the cation binding pocket (11,15,20).…”
supporting
confidence: 76%
See 1 more Smart Citation
“…The true effect on Na ϩ binding to E 1 may actually be more pronounced than revealed by the 3-fold decrease in apparent affinity, because it is masked by displacement of the conformational equilibrium in favor of E 1 . The 3-fold reduction or more of Na ϩ affinity is of the same magnitude as previously detected for some of the mutants with alterations to residues proposed to contribute to coordination of Na ϩ in the cation binding pocket (11,15,20).…”
supporting
confidence: 76%
“…Previous mutational studies of P-type ATPases have pinpointed highly conserved residues with oxygen-containing side chains in transmembrane segments M4, M5, and M6 as essential to cation binding and occlusion (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The high-resolution crystal structure of the Ca 2ϩ -ATPase with bound Ca 2ϩ revealed that indeed these residues donate Ca 2ϩ ligands in the binding pocket (2).…”
mentioning
confidence: 99%
“…DISCUSSION We have taken advantage of the functional differences and the high degree of sequence homology between the H,K-and Na,K-ATPases to attempt to identify the determinant of the electrogenicity of cation transport by the group IIc P-ATPases. In the fifth transmembrane segment, several amino acid residues have been shown to play a role in cation binding in both the H,K-and Na,K-ATPases (22,23,(25)(26)(27)(28)(29)(30)(31) and also in SERCA (32). The middle of the fifth transmembrane segment region is highly similar between the H,K-and Na,K-ATPases (Fig.…”
Section: Electrogenic Transport By the Lys 800 Mutants Of The Hkatpamentioning
confidence: 90%
“…Only the S782A mutant had a very small but significant 86 Rb uptake of 2.6 Ϯ 1.1 pmol/min, whereas the wild-type Na,KATPase expressed a transport activity of 45.1 Ϯ 8.6 pmol/min, similar to that of the wild-type H,K-ATPase. A low affinity for extracellular K ϩ has been observed with mutants of the corresponding position (Ser 775 ) in ␣ 1 Na,K-ATPase from other species (21)(22)(23). Assuming a similar effect of homologous mutations in the Bufo ␣ 1 Na,K-pump, we studied the transport function of the Ser 782 mutants at a higher (40 mM) concentration of K ϩ .…”
Section: Expression Of the B Marinus Nak-and Hk-atpase Mutants-mentioning
confidence: 92%
“…During ATP hydrolysis, Ptype ATPases are phosphorylated at a highly conserved aspartate residue (Axelsen and Palmgren, 1998). Na þ /K þ ATPase is composed of two mandatory subunits, the a and b subunits (Jorgensen and Pedersen, 2001). The a subunit contains 10 transmembrane segments, including Na þ /K þ ion binding domains, cytoplasmic phosphorylation sites, inhibitor (ouabain and digitoxin) and activator binding domain (Kaplan, 2002).…”
Section: Naþ/kþ Atpasementioning
confidence: 99%